How do RNA molecules distinguish self from non-self? - Ofer Kimchi; Kira Mitchel; Andrew G. T. Pyo; Ned S. Wingreen; Elizabeth R. Gavis (Proceedings of the National Academy of Sciences, 2026)
RNA molecules form homotypic clusters in a variety of contexts. mRNAs enriched in germ granules in Drosophila embryos are a canonical example, with polar granule component ( pgc ) mRNAs colocalized with other pgc mRNAs, and nanos mRNAs with other nanos mRNAs. The observation of homotypic clustering poses a conundrum: how can RNAs of a given sequence distinguish other RNAs of the same sequence from those with different sequences? Here we show in silico that RNAs can distinguish self from non-self through the presence of palindromic regions within RNA sequences, and that palindromes can mediate homotypic clustering. We further show that RNA–RNA interactions are unlikely to lead to homotypic clusters in the absence of palindromes due to a competition between intra- and intermolecular RNA structures. We explore the implications of the palindrome-based clustering hypothesis for nanos and pgc mRNAs, and suggest how it may clear up a surprising feature of nanos clusters. More broadly, our results indicate that the palindrome content of RNAs may be under evolutionary selection pressure across a range of contexts.